ONLINE LEARNING: AN ANALYSIS OF MOTIVATION PAI LEARNING: PEMBELAJARAN ONLINE: ANALISIS TERHADAP MOTIVASI PEMBELAJARAN PAI - Mazrur, Mazrur; Surawan, Surawan (Anterior Jurnal, 2023)
The importance of learning motivation is as a form of encouragement in learning that arises in students consciously to carry out learning activities, making it easier to achieve learning goals in PAI subjects at SMP Muhammadiyah. The purpose of this study is to determine the motivation to learn. This type of research is mixed methods, which is the subject of 67 grade VIII students of SMPN 8 Palangka Raya and the informant is a PAI teacher. Data collection techniques are using questionnaires, interviews, and documentation. Data validation techniques use source triangulation, tabulation techniques and percentages, while data analysis uses data reduction, data presentation and verification. The results showed that student motivation in learning PAI at SMPN 8 Palangka Raya with a low level of 32.83%, a medium level of 44.77%, a high level of 20.89% and a very high level of 1.49%. So it can be concluded that overall student motivation in participating in PAI learning is 74.82% included in the medium motivation category. The intrinsic factors that affect student motivation include student perseverance in participating in PAI learning, feeling needed in PAI Learning and the existence of hopes and aspirations with PAI learning. While extrinsic factors such as a conducive learning environment, teachers who teach PAI learning and facilities in PAI learning.